Do Pigs Have Adequate Space in Animal Transportation Vehicles?—Planimetric Measurement of the Floor Area Covered by Finishing Pigs in Various Body Positions - Arndt, Heidi; Volkmann, Nina; Spindler, Birgit; Hartung, Jörg; Kemper, Nicole (Frontiers in Veterinary Science, 2019)
In this study, the floor area covered by individual finishing pigs in various body positions was measured using a contrast-based planimetric method for computer-assisted analysis of two-dimensional images. 232 finishing pigs were weighed during the last fifth of the fattening period and measured in different body positions using contrast based planimetry. Thirteen body positions were defined based on characteristic directions of the head, legs and body. The lowest average covered floor area was found for body position A (pig standing up straight, nose touching the ground) with 0.288 ± 0.026 m2. The highest average covered floor area for a standing pig amounted to 0.335 ± 0.030 m2 in body posture ES (pig standing curved sideways, head raised above the dorsal line) and for a lying pig, measuring 0.486 ± 0.040 m2 (posture LL, pig lying in fully lateral recumbent position). The covered floor surface significantly depended on the weight of the animal and the body posture. It was found that allometric estimations previously described for calculating the floor area physically covered by a pig’s body are not consistently precise in depicting the actual areas covered. Moreover, it was shown that the minimal floor area offered in animal transportation vehicles, according to European legislation, is insufficient in the case of all pigs lying in the fully recumbent position simultaneously, without the pigs being forced partially overlap one another. Therefore, both, allometric formulas and legislation should be modified on the basis of these results and further studies with pigs of modern genetic origin should be conducted.